Migration process experience and its impact on well-being among women immigrants in Indonesia - Selian, Sri Nurhayati; Khalefa, Eslam Younis; Hanifah, Lena (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
Women and children in many countries are forced to migrate due to prolonged civil wars and conflicts. The factors and conditions that affect the well-being of immigrant and refugee populations residing in host countries are not widely known. This study aims to identify and explore the personal experiences and migration processes that affect the well-being of immigrant women in Indonesia. A qualitative method and case study design were implemented. Eight refugee women from three different countries were interviewed: Somalia, Palestine, and Afghanistan. It was found that the contexts of identification, personal experiences, the migration process, and the motives or triggers for migration were important factors in influencing the women’s present and future well-being. The study provides implications for the theory of the model used. The application of the theory assisted the researchers to construct a conceptual framework of the subjective well-being of immigrant women.